2006
DOI: 10.1515/bc.2006.102
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the human tissue kallikrein genes KLK4, 5, 6, and 7 increases the malignant phenotype of ovarian cancer cells

Abstract: The human tissue kallikrein family of serine proteases (hK1-hK15 encoded by the genes KLK1-KLK15) is involved in several cancer-related processes. Accumulating evidence suggests that certain tissue kallikreins are part of an enzymatic cascade pathway that is activated in ovarian cancer and other malignant diseases. In the present study, OV-MZ-6 ovarian cancer cells were stably co-transfected with plasmids expressing hK4, hK5, hK6, and hK7. These cells displayed similar proliferative capacity as the vector-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 30 publications
4
75
0
3
Order By: Relevance
“…More precisely, the transfection of OV-MZ-6 ovarian cancer cells to stably express KLK4, KLK5, KLK6, and KLK7 resulted in their increased invasiveness in vitro . Additionally, infusion of the transfected ovarian cancer cells increases tumor burden in vivo , highlighting their signifi cance in ovarian cancer progression (Prezas et al , 2006 ). This effect could partially be explained by the ability of KLK5 (Michael et al , 2005 ), KLK6 (Bernett et al , 2002 ;Magklara et al , 2003 ), and KLK7 to degrade ECM proteins, whereas KLK4 promotes this degradation indirectly by the activation of the uPA-uPAR-MMPs axis (Takayama et al , 2001 ).…”
Section: Kallikrein-related Peptidases and Tumor Progressionmentioning
confidence: 99%
“…More precisely, the transfection of OV-MZ-6 ovarian cancer cells to stably express KLK4, KLK5, KLK6, and KLK7 resulted in their increased invasiveness in vitro . Additionally, infusion of the transfected ovarian cancer cells increases tumor burden in vivo , highlighting their signifi cance in ovarian cancer progression (Prezas et al , 2006 ). This effect could partially be explained by the ability of KLK5 (Michael et al , 2005 ), KLK6 (Bernett et al , 2002 ;Magklara et al , 2003 ), and KLK7 to degrade ECM proteins, whereas KLK4 promotes this degradation indirectly by the activation of the uPA-uPAR-MMPs axis (Takayama et al , 2001 ).…”
Section: Kallikrein-related Peptidases and Tumor Progressionmentioning
confidence: 99%
“…Assessment of KLK protein dysregulation in ovarian cancer was compiled from the results of 17 studies (Dong et al, 2001;Luo et al, 2001Luo et al, , 2003Tanimoto et al, 2001;Hoffman et al, 2002;Yousef et al, , 2003bBorgono et al, 2003;Diamandis et al, 2003;Ni et al, 2004;Scorilas et al, 2004;Xi et al, 2004;Prezas et al, 2006;Shan et al, 2007;Bayani et al, 2008;Shaw and Diamandis, 2008). Chromosomal aberration in ovarian cancer was extracted from the Progenetix comparative genomic hybridisation database available as of January 2009 (Baudis and Cleary, 2001).…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…At least seven kallikrein proteins are up-regulated in ovarian cancer compared with normal ovarian tissues (Yousef et al, 2003b). The prognostic value of at least 11 out of 15 members of the human kallikrein family in ovarian cancer has been also published (Clements et al, 2004;Yousef et al, 2005;Prezas et al, 2006;Dorn et al, 2007). Six kallikreins, KLK4, KLK5, KLK6, KLK7, KLK10, and KLK15 (Kim et al, 2001;Kyriakopoulou et al, 2003;Shvartsman et al, 2003;Yousef et al, 2003c;Kountourakis et al, 2008), are markers of poor prognosis in ovarian cancer.…”
mentioning
confidence: 99%
“…Substrates for KLK6 include collagen I and IV, fibrinogen, fibronectin and laminin Blaber et al, 2002;Borgono and Diamandis, 2004). Prezas et al (2006) demonstrated that ovarian cells stably transfected to express KLK4, 5, 6 and 7 were significantly more invasive in vitro and formed larger tumors in mice. KLK6 overexpression has also recently be shown to increase skin cell migration and invasion (Klucky et al, 2007).…”
Section: Introductionmentioning
confidence: 99%